Immunohistochemical staining with non-phospho β-catenin as a diagnostic and prognostic tool of COX-2 inhibitor therapy for patients with extra-peritoneal desmoid-type fibromatosis - Tomohisa Sakai; Yoshihiro Nishida; Shunsuke Hamada; Hiroshi Koike; Kunihiro Ikuta; Takehiro Ota; Naoki Ishiguro (BMC, 2017)
Abstract Background Immunohistochemical staining with conventional anti-β-catenin antibody has been applied as a diagnostic tool for desmoid-type fibromatosis (DF). This study aimed to evaluate the diagnostic and prognostic value of immunohistochemical staining with anti-non-phospho β-catenin antibody, which might more accurately reflect the aggressiveness of DF, in comparison to the conventional anti-β-catenin antibody. Methods Between 2003 and 2015, 40 patients with extra-peritoneal sporadic DF were prospectively treated with meloxicam or celecoxib, a COX-2 inhibitor, therapy. The efficacy of this treatment was evaluated according to Response Evaluation Criteria in Solid Tumors (RECIST). Immunohistochemical staining was performed on formalin-fixed material to evaluate the expression of β-catenin and non-phospho β-catenin, and the positivity was grouped as negative, weak, moderate, and strong. DNA was isolated from frozen tissue or formalin-fixed materials, and the CTNNB1 mutation status was determined by direct sequencing. Results Of the 40 patients receiving COX-2 inhibitor treatment, there was one with complete remission, 12 with partial remission, 7 with stable disease, and 20 with progressive disease. The mutation sites in CTNNB1 were detected in 22 (55%) of the 40 cases: T41A (17 cases), S45F (3 cases), and T41I and S45P (1 each). The positive nuclear expression of non-phospho β-catenin showed a significant correlation with positive CTNNB1 mutation status detected by Sanger method (p = 0.025), and poor outcome in COX-2 inhibitor therapy (p = 0.022). In contrast, nuclear expression of β-catenin did not show a significant correlation with either CTNNB1 mutation status (p = 0.43) or outcome of COX-2 inhibitor therapy (p = 0.38). Conclusions Nuclear expression of non-phospho β-catenin might more appropriately reflect the biological behavior of DF, and immunohistochemical staining with non-phospho β-catenin could serve as a more useful diagnostic and prognostic tool of COX-2 inhibitor therapy for patients with DF.